2014
DOI: 10.1002/bse.1874
|View full text |Cite
|
Sign up to set email alerts
|

How Do Strengths and Weaknesses in Corporate Social Performance Across Different Stakeholder Domains Affect Company Performance?

Abstract: The existing research on corporate social responsibility (CSR) has largely focused on the positive aspect of corporate social performance (CSP) and company performance (CP) and ignored the relationship between actions that would qualify as negative CSP (or weakness in CSP) towards a stakeholder group and company performance. Using data from the KLD collected over a three-year period, this study examines the relationship between both CSP weaknesses and strengths and CP across individual stakeholder domains. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 62 publications
0
31
0
6
Order By: Relevance
“…In addition, ineffective or exceedingly opportunistic CSR policies create negative sentiments among stakeholder groups that could potentially harm or extensively damage a firm's legitimacy and social licence to operate in the community (Tang‐Lee, ). This is also evident in the study of Kumar, Boesso, and Michelon () which revealed that strengths in CSR related to primary stakeholder domains are associated with superior company performance. However, this relationship is tenuous, at best, in the case of the secondary stakeholder domain.…”
Section: Introductionmentioning
confidence: 66%
“…In addition, ineffective or exceedingly opportunistic CSR policies create negative sentiments among stakeholder groups that could potentially harm or extensively damage a firm's legitimacy and social licence to operate in the community (Tang‐Lee, ). This is also evident in the study of Kumar, Boesso, and Michelon () which revealed that strengths in CSR related to primary stakeholder domains are associated with superior company performance. However, this relationship is tenuous, at best, in the case of the secondary stakeholder domain.…”
Section: Introductionmentioning
confidence: 66%
“…As such, it complements prior studies on stakeholder salience, by focusing on the power to influence the company (Mitchell et al , ; Grafé‐Buckens and Hinton, ; Henriques and Sharma, ; González‐Benito and González‐Benito, ; Bolton and Landells, ) by showing that organized, collective and public stakeholder power can affect investors' decisions and thus corporate financial performance. We also contribute to the social and environmental accounting literature and stakeholder engagement stream (Unerman and Bennett, ; Onkila, ; Boesso et al , ; Dobele et al , ; Rodrigue, ; Amran et al , ; Rodrigue et al , ; Kumar et al , ) by considering a new form of engagement that may have the potential to affect firms' behavior via changing investors' decisions in the stock market. Finally, our research shows the impacts of SMe activism in the current socio‐economic context, with the growth of social movement protests in Southern Europe (Sampedro and Lobera, ), and the development of social networks as predominant communication channels, which have remarkably enhanced and transformed social movements (Anduiza et al , ).…”
Section: Introductionmentioning
confidence: 84%
“…We also found that positive indirect signals related to the employee and customer dimensions of CSP had stronger effects on firm value than positive indirect signals related to other CSP dimensions, and that, over time, indirect signals related to diversity have had a more positive impact on firm value. These results are largely in line with recent prior studies that have examined the effect of direct CSP signals related to the seven aforementioned CSP dimensions on firm performance (Kumar et al ., ; Lawal et al ., ; Michelon et al ., ). Interestingly, we found that shareholders' reactions to negative indirect signals did not vary as a function of the specific social domain repudiated by signals from a third party.…”
Section: Discussionmentioning
confidence: 99%